Enhanced value and profitability premium : Evidence from the U.S. market - Hankala, Miikka (My University, 2022)
Value and profitability premiums are market anomalies that challenge the efficient market hypothesis. Despite the extensive literature on value and profitability, the recently proposed investment strategy that combines value and profitability seems even more robust. This strand of literature suggests that value and profitability strategies are best used in combination with each other and that combining these two effects earns superior performance. Regardless of how attractive value and profitability are together, much uncertainty still exists about what combination of value and profitability earns the best performance. This study investigates the performance of portfolios that combine value and profitability in the U.S. markets. The data encompasses stocks in the S&P 500 index over the sample period from 2000 to 2021. The main objective of this study is to determine whether profitable value stocks achieve higher risk-adjusted returns than unprofitable growth stocks. Moreover, our innovation for this study is to utilize the most recent research on value and profitability premium. Motivated by the recent literature, the profitability ratios used in this study are gross profitability (GP) and cash profitability (CP). Following the recent findings on value premium, this study uses retained earnings-to-market (RE/ME) and earnings before interest and taxes-to-enterprise value (EBIT/EV) ratios as proxies for value. To test different strategies, the aim is to find the portfolio that provides the best combination of value and profitability. Finally, the secondary objective is to assess how the performance of combination strategies compares against the traditional value and profitability portfolios. The results show that portfolios that invest in profitable value stocks generate much higher risk-adjusted returns than portfolios that invest in unprofitable growth stocks in the S&P 500 index. Among combinations, the best overall performance is observed for the GP & RE/ME portfolio. The results for the GP & RE/ME portfolio are persistent and statistically significant across all asset pricing models used in this study. Moreover, the results show that the additional screen on profitability dramatically enhances the performance of traditional value strategies. The study finds that an additional screen on value improves the performance of traditional CP strategy but finds no evidence of improvement in the case of GP strategy. However, this study finds that combining profitability with value enhances the performance of traditional long-short portfolios, even in the case of GP strategy. Overall, these findings suggest that the strategy that goes long on profitable value and short on unprofitable growth earns the best performance.

Arvo- ja kannattavuuspreemiot ovat markkina-anomalioita, jotka haastavat tehokkaiden markkinoiden hypoteesin. Arvo- ja kannattavuuspreemiot viittaavat ilmiöön, jonka mukaan matalan arvostuksen ja korkean kannattavuuden yhtiöt tuottavat korkeampia riskikorjattuja osaketuottoja kuin korkean arvostuksen ja matalan kannattavuuden yhtiöt. Laajasta emprisiisestä tutkimuksesta huolimatta aiempi kirjallisuus on keskittynyt pääosin tutkimaan arvo- ja kannattavuusstrategieoita erikseen. Uudempi kirjallisuus kuitenkin osoittaa, että arvo- ja kannattavuusstrategoita yhdistämällä voidaan saavuttaa korkeampia riskikorjattuja osaketuottoja. Empiirinen tutkimus ei ole kuitenkaan löytänyt konsensusta kysymykselle mitkä arvo- ja kannattavuusstrategiat toimivat parhaiten yhdessä. Tämä tutkielma tutkii arvo- ja kannattavuusstrategioihin perustuvia yhdistelmästrategioita Yhdysvaltojen osakemarkkinoilla. Tutkielman aineisto koostuu S&P 500 -indeksin yhtiöstä ja se on kerätty vuosilta 2000-2021. Tutkielman tarkoitus on selvittää tuottavatko korkean kannattavuuden arvo-osakket parempia riskikorjattuja tuottoja kuin matalan kannattavuuden kasvuosakkeet. Tämä tulkielma erottuu aikaisemmasta kirjallisuudesta yhdistämällä uusimmat empriiset löydökset arvo- ja kannattavuuspreemioiden kirjallisuudesta. Tuoreimman kirjallisuuden motivoimana tässä tutkielmassa kannattavuusstrategioita edustavat bruttokannattavuus (GP) ja kassavirtapohjainen operatiivinen kannattavuus (CP). Arvostrategioita tässä tutkielmassa edustavat akateemiset RE/ME ja EBIT/EV -strategiat. Tutkielman ensisijaisena tarkoituksena on löytää kombinaatio, joka tuottaa parhaan mahdollisen yhdistelmän valituista arvo- ja kannattavuusstrategioista. Tutkielman toissijaisena tarkoituksena on verrata yhdistelmästrategioiden riskikorjattuja tuottoja perinteisten arvo- ja kannattavuusstrategioiden kanssa. Tutkimuksen tulokset osoittavat, että kannattavat arvo-osakkeet tuottavat parempia riskikorjattuja kuin matalan kannattavuuden kasvuosakkeet S&P 500 -indeksissä. Yhdistelmästrategioista korkeimmat riskikorjatut tuotot havainnoitiin GP & RE/ME -strategialla. GP & RE/ME -strategian riskikorjatut ylituotot ovat positiviisia ja tilastollisesti merkitseviä kaikilla tämän tutkimuksen regressiomalleilla tarkasteltuna. Lisäksi tutkimus osoittaa, että yhdistelmästrategiat tuottavat korkeampia riskikorjattuja tuottoja kuin perinteiset arvostrategiat. Yhdistelmästrategoiden riskikorjatut tuotot ovat korkeampia kuin CP-strategian riskikorjatut tuotot, mutta matalampia kuin GP-strategialla. Siitä huolimatta markkinaneutraalit (long/short) yhdistelmästrategiat ansaitsevat korkeampia riskikorjattuja tuottoja kuin markkinaneutraali GP-strategia. Tuloksien perusteella voidaan todeta, että markkinaneutraali strategia, joka ostaa kannattavia arvo-osakkeita ja myy lyhyeksi matalan kannattavuuden kasvuosakkeita tuottaa parhaan riskikorjatun lopputuloksen.
Keywords: fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; Master's Degree Programme in Finance